Switchable Multi-Wavelength Thulium-Doped Fiber Laser Using Four-Mode Fiber Based Sagnac Loop Filter - Ying Guo (IEEE Photonics Journal, 2020)
A switchable multi-wavelength thulium-doped fiber laser (TDFL) using a four-mode fiber based Sagnac loop filter was proposed and demonstrated. The Sagnac loop, incorporating a 4.8 m long four-mode step-index fiber, acting as a comb filter was analyzed theoretically and experimentally. By adjusting two polarization controllers, eight stable single-wavelength operations and five stable dual-wavelength operations were obtained with easy switching between the different operation modes. The wavelength range covered during the single-wavelength switchable operation with a signal-to-noise ratio of up to 55 dB was ~28.51 nm. In dual-wavelength switchable operation, the maximum and minimum wavelength spacings were ~21.78 nm and ~1.50 nm, respectively. Due to the abundant wavelength resources, the proposed TDFL has great potential in wavelength division multiplexing free-space optical communications, optical fiber sensing, and photonic generation of microwave signals.